Effect of Fermentation on Structural Characteristics and Bioactive Compounds of Bee-Pollen Based Food - Zuluaga-Dominguez, Carlos M.; Quicazan, Marta (Journal of Apicultural Science, 2019)
Bee-pollen is a product of the hive which has had a growth in consumption in recent years due to the recognition of its nutritional and bioactive potential. However, several reports have shown that the external structure of the grain limits the absorption of nutrients in the human gastrointestinal tract. A structural modification could be achieved through fermentative processes, favoring the release of compounds found inside this food, in addition to obtaining a product with potential probiotic characteristics. The objective of this work was to evaluate how fermentation through the inclusion of yeasts of the species , bacteria of species or a commercial culture Choozit affeccted such parameters as Scanning Electron Microscopy (SEM), Differential Scanning Calorimetry (DSC), phenolic compounds, flavonoids and antioxidant activity. The results found that the use of consortia between yeast and lactic acid bacteria significantly increased in such characteristics as total phenolics and antioxidant activity by 31% and 39% respectively. The analysis by DSC showed an increase in the heat flow of the fermented products compared to fresh bee-pollen, which could indicate structural modification caused by the activity of microorganisms, a fact made visible through micrographs obtained by Scanning Electron Microscopy.